How enemies become friends : the sources of stable peace - Kupchan, Charles (Princeton studies in international history and politics., 2010)
Is the world destined to suffer endless cycles of conflict and war? Can rival nations become partners and establish a lasting and stable peace? How Enemies Become Friends provides a bold and innovative account of how nations escape geopolitical competition and replace hostility with friendship. Through compelling analysis and rich historical examples that span the globe and range from the thirteenth century through the present, foreign policy expert Charles Kupchan explores how adversaries can transform enmity into amity--and he exposes prevalent myths about the causes of peace. Kupchan conten.